Anxiety Of Maryam In Okky Madasari The Outcast Novel (2012): A Psychoanalytic Approach - Cahyaningsih, Agustin; , Dr. Phil. Dewi Candraningrum, S.Pd., M.Ed; , Titis Setyabudi, S.S., M.Hum (2015)
This research paper aims to know the anxiety of Maryam in Okky Madasari's The Outcast novel related with psychoanalytic approach. The objective of the research is to analyze anxiety of Maryam in The Outcast novel by using Psychoanalytic approach. The type of this research is descriptive qualitative. The primary data of the research is The Outcast novel by Okky Madasari. The secondary data of the research are taken from any information related to the novel from other books, and internet. The techniques of collecting data are reading the novel, taking notes of important part in both primary and secondary data, underlying the important words, phrases, sentences, arranging the data into several part based on its classification, selecting the data by rejecting the irrelevant information which does not support the topic of the study, and drawing the conclusion. The method to analyze this data is descriptive analysis. Anxiety of Maryam appears in three forms, realistic anxiety related with her worries and her character, Maryam becomes a quite person. Neurotic anxiety where Maryam tries to make a perfect decision in her life and moral anxiety where Maryam feels guilty and worries about what just she makes.